2012
DOI: 10.1159/000341677
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Reduced-Port Laparoscopic Distal Gastrectomy for Gastric Cancer: A Pilot Study

Abstract: Background/Aims: Single-port and reduced-port laparoscopic surgeries are performed as a less invasive form of surgery than conventional laparoscopy. In this study, short-term patient outcomes were compared between reduced-port laparoscopic distal gastrectomy (RPLDG) and conventional laparoscopy-assisted distal gastrectomy (LADG) to evaluate the feasibility of RPLDG for gastric cancer. Methods: Between August 2010 and July 2011, 38 patients underwent LADGs that were performed by a single surgeon. Of these, 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
(17 reference statements)
3
27
0
Order By: Relevance
“…We showed similar surgical outcomes in a previous study for a reduced-port laparoscopic distal gastrectomy (RPLDG) procedure, using a multiaccess port at the umbilicus plus one additional port, compared with conventional LADG (CLADG), using five ports plus a small, 5-cm skin incision [14]. Patients who underwent RPLDG were particularly satisfied with the cosmetic appearance of the surgical wounds.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We showed similar surgical outcomes in a previous study for a reduced-port laparoscopic distal gastrectomy (RPLDG) procedure, using a multiaccess port at the umbilicus plus one additional port, compared with conventional LADG (CLADG), using five ports plus a small, 5-cm skin incision [14]. Patients who underwent RPLDG were particularly satisfied with the cosmetic appearance of the surgical wounds.…”
Section: Introductionsupporting
confidence: 69%
“…An experienced and skillful surgeon can perform such complex laparoscopic gastrectomies after gaining sufficient experience of conventional laparoscopic gastrectomies. In our previous study [14], we also reported satisfactory outcomes for reduced-port (SILS Port TM plus one port) LADG.…”
Section: Discussionmentioning
confidence: 51%
“…After the benefits of MIS are confirmed in these studies, laparoscopic surgery for EGC could be recognized, not as an investigational approach, but as a standard procedure in clinical practice. With the accumulated and extensive experiences and improved surgical instruments, some surgeons are now focusing on reducing the patient's distress by using reduced ports or a single incision approach for EGC 26,27. Extracorporeal anastomoses using minilaparotomy is being replaced by intracorporeal anastomoses and results in a totally laparoscopic gastrectomy 28,29,30,31,32.…”
Section: Mis For Early Gastric Cancermentioning
confidence: 99%
“…Technically-demanding procedures such as total gastrectomy with or without splenectomy, gastrectomy with multivisceral resection, and completion total gastrectomy for remnant gastric cancer have been successfully performed by experienced surgeons using minimally invasive approaches 64,65,66,67,68. Single incision or reduced port surgery for gastric cancer also has been reported to be a safe and feasible procedure 26,27. Although this approach is safe and feasible, more evidence that demonstrates efficacy is needed.…”
Section: Mis For Technically-demanding Proceduresmentioning
confidence: 99%
“…[9][10][11] Dual-incision laparoscopic surgery (DILS) has been reported in several surgical fields. [12][13][14][15] Compared with conventional laparoscopic surgery, DILS reduced the number of trocars and offered less pain, shorter length of incision, quicker recovery, and better cosmetic appearance. However, no report has yet been proposed about the effectiveness of DILS in PD catheter implantation (DILS-PD).…”
Section: Introductionmentioning
confidence: 99%